Functional Outcome of Arthroscopic Anterior Cruciate Ligament Reconstruction Using Quadriceps Tendon Autograft - Varrdhaman H Dhariwal; Ashokan Chandran; Aravinth Thamizholi; Ajith Kumar; Mohan K Kannaiyan (Journal of Orthopedics and Joint Surgery)
Aims and background: To analyze the functional outcomes of anterior cruciate ligament (ACL) reconstruction arthroscopically using a quadriceps tendon (QT) graft, the assessment is conducted based on standardized scoring systems. Functional outcomes are measured using the Tegner–Lysholm (TL) score and International Knee Documentation Committee (IKDC) score, which provide an in-depth evaluation of knee function and patient recovery. Materials and methods: A detailed history of knee instability was obtained, and a relevant clinical examination was performed during the screening visit to assess eligibility based on the grade of anterior tibial translation over the femur. Additional clinical tests were conducted simultaneously to exclude other potential ligament injuries. Patients aged 18 years and above with grade III anterior tibial translation were included in the study. Radiological confirmation through X-ray and magnetic resonance imaging (MRI) was obtained to support the diagnosis. ACL reconstruction was performed by arthroscopic method using a QT graft. Postoperatively, all patients were monitored, and functional knee assessment scores were recorded and compared with preoperative values. Results: TL score showed improvement from preoperative mean score of 54.6 to 86.2 in 6 weeks and 94.8 in 1-year follow-up with confidence interval of 95% and p < 0.05. The subjective IKDC score showed improvement from preoperative mean score of 52.5 to 84.4 in 6 weeks and 93.8 in 1-year follow-up with confidence interval of 95% and p < 0.05. Conclusion: The QT graft is a reliable option for primary arthroscopic ACL reconstruction. Findings from our study indicate that its clinical outcomes are comparable to those reported in studies utilizing other graft options for primary ACL reconstruction. The selection of the graft should be based on criteria such as the age of the patient, occupation, and activity level, with a shared decision-making approach between the surgeon and the patient. Clinical significance: To find out the clinical outcomes of quadriceps graft among the multiple other grafts available for primary ACL reconstruction.